Dilemmas of recognition and redistribution: Constituting intersectional subjects of inclusion in migrant support work - Kangas‐Müller, Laura (Gender, work, and organization, 2024)
In this study, I explore how the subject of inclusion is constituted as intersectional in the organizational discursive practices of a civil society organization promoting migrant and refugee inclusion. Drawing on Crenshaw's notion of political intersectionality and Fraser's politics of recognition and redistribution, I analyze the political dimension of an inclusion project by showing how intersectional categories are connected to differentiated struggles and strategies of inclusion. The ethnographic study illustrates how two subject positions are constituted as being underpinned by either the logic of recognition or redistribution. Moreover, the findings show how the two strategies interact, revealing the dynamics of privilege and disadvantage at play in the inclusion project. The paper contributes to critical studies on inclusion and intersectionality in organizational contexts by extending our understanding of power dynamics and tensions as integral parts of the intersectional approach.